Isolation of toxoplasma gondii from the keel-billed toucan (Ramphastos sulfuratus) from Costa Rica - Dubey, J. P. (2009)
Pectoral muscles from a captive keel-billed toucan (Ramphastos sulfuratus) from Costa Rica were fed to a Toxoplasma gondii– free cat, and the cat shed oocysts. Laboratory mice fed these oocysts developed antibodies to T. gondii in their sera and T. gondii tissue cysts in their brains. The DNA extracted from the brains of infected mice was characterized using 10 polymerase chain reaction–restricted fragment length polymorphic markers (SAG1, SAG2, SAG3, BTUB, GRA6, c22-8, c29-2, L358, PK1, and Apico). The isolate designated TgRsCr1 was found to be non-clonal with Type I, II, and III alleles at different loci. This is the first isolation of T. gondii from this host.